2013
DOI: 10.4049/jimmunol.1302121
|View full text |Cite
|
Sign up to set email alerts
|

Heteromeric Complexes of Native Collectin Kidney 1 and Collectin Liver 1 Are Found in the Circulation with MASPs and Activate the Complement System

Abstract: The complement system is an important part of the innate immune system. The complement cascade may be initiated downstream of the lectin activation pathway upon binding of mannan-binding lectin, ficolins, or collectin kidney 1 (CL-K1, alias CL-11) to suitable microbial patterns consisting of carbohydrates or acetylated molecules. During purification and characterization of native CL-K1 from plasma, we observed that collectin liver 1 (CL-L1) was copurified. Based on deglycosylation and nonreduced/reduced two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
130
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 35 publications
10
130
0
Order By: Relevance
“…It was reported that interchain disulphide bonds held together the CL-10 and CL-11 single chains, implying that such heterotrimers can only form within a cell that synthesized both components (34). So far, the only known cell in which CL-11 and CL-10 are coexpressed is the hepatocyte.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that interchain disulphide bonds held together the CL-10 and CL-11 single chains, implying that such heterotrimers can only form within a cell that synthesized both components (34). So far, the only known cell in which CL-11 and CL-10 are coexpressed is the hepatocyte.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that the novel CL CL-10 (also known as CL-L1) could be a possible candidate in the family comprising circulating MASP binding partners (31); however, we assume that depletion of CL-11 also will include depletion of CL-10 because both CLs reportedly bind to mannose (32). Moreover, it has recently been shown that CL-10 and CL-11 peptide chains presumably form complexes, thus depletion of one of the molecules will lead to depletion of the other (33). It should be mentioned that depletion was verified in ELISA assays using lower serum concentrations than the concentration applied for complex measurements because higher serum concentrations would exceed the limit for these assays.…”
Section: Discussionmentioning
confidence: 99%
“…CL-L1 is encoded by the COLEC10 gene and is primarily expressed in the liver, placenta, and adrenal glands (18). Initially, CL-L1 was identified as a cytosolic protein but has now been found in the circulation, where it complexes with MBL-associated serine proteases (MASPs), the enzymes responsible for activation of complement through the lectin pathway (21,22,26). In healthy individuals, CL-L1 levels appear to be present at near adult levels at birth and show low variation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a limitation of our study is that we only showed associations, with no evidence of causality. Secondly, the measurements we performed are primarily of Articles hetero-oligomers between CL-L1 and CL-K1 polypeptide chains, two collectins that have most likely evolved from the same ancestral gene by gene duplication (21,26,29). We have observed that there is a tight correlation between the amount of CL-L1 and CL-K1 in plasma but no one has studied in detail whether both molecules can be present separately at different sites in the body and whether such proteins appear in plasma at extreme conditions (24,26,29,30).…”
Section: Discussionmentioning
confidence: 99%